PEMIKIRAN DAN PERADABAN ISLAM DINASTI UMAYYAH DAN ABBASIYAH: KAJIAN HISTORIS DAN RELEVANSI WARISAN INTELEKTUAL DAN PERADABAN ISLAM DALAM DUNIA KONTEMPORER - Hazim, Muhamad; Firmansyah, Herdi; Tajudin Zuhri, M; Munawaroh, Nenden (LPPM STAI Muhammadiyah Probolinggo, 2025)
This articles the significant contributions of Islamic civilization and thought during the Umayyad and Abbasid dynasties to the development of global knowledge and intellectual progress. The Umayyad Dynasty (661–750 CE), centered in Damascus, initiated massive territorial expansion that fostered cross-cultural interactions and the early codification of Islamic sciences such as tafsir and hadith. Monumental architecture, centralized administration, and the institutionalization of Arabic as the official language laid a strong foundation for intellectual continuity. In contrast, the Abbasid Dynasty (750–1258 CE), based in Baghdad, marked the peak of Islamic civilization's golden age. The establishment of Bayt al-Hikmah (House of Wisdom) and the translation movement from Greek, Persian, and Indian sources catalyzed not only the transfer but also the advancement of knowledge, forming the basis of many modern sciences. Intellectual figures such as Al-Khwarizmi, Ibn Sina, and Al-Farabi symbolize Islam’s contributions to mathematics, medicine, and philosophy. Using a qualitative-historical approach through library research, this study investigates the intellectual legacy of these two dynasties and their relevance in contemporary global contexts. The analysis includes their impact on science, governance, cultural tolerance, and sustainable development. The findings demonstrate that the integration of spiritual values, scientific rationalism, and cultural inclusivity during these periods provided an ideal model for building a civilized, tolerant, and knowledge-based society. These intellectual heritages remain highly relevant in addressing modern global challenges and in shaping a future civilization that is inclusive, ethical, and sustainable.